Citrulline induces fatty acid release selectively in visceral adipose tissue from old rats. Issue 9 (10th June 2014) - Joffin, Nolwenn; Jaubert, Anne‐Marie; Durant, Sylvie; Bastin, Jean; De Bandt, Jean‐Pascal; Cynober, Luc; Moinard, Christophe; Forest, Claude; Noirez, Philippe
<x xml:space="preserve">Abstract</x> Scope During aging, increased visceral adipose tissue (AT) mass may result in impaired metabolic status. A citrulline (CIT)‐supplemented diet reduces AT mass in old rats. We hypothesized that CIT could directly affect fatty acid (FA) metabolism in retroperitoneal AT. Methods and results A 24‐h exposure of AT explants from old (25 months) rats to 2.5 mM CIT induced a 50% rise in glycerol and FA release, which was not observed in explants from young (2 months) animals. The phosphorylated form of hormone‐sensitive lipase, a key lipolytic enzyme, was 1.5‐fold higher in CIT‐treated explants from old and young rats, whereas glyceroneogenesis, that provides glycerol‐3P requested for FA re‐esterification, and its key enzyme phosphoenolpyruvate carboxykinase, were down‐regulated 40–70%. Specifically in young rats, beta‐oxidation capacity and gene expressions of carnitine palmitoyl transferase 1‐b and very long chain acyl‐CoA dehydrogenase were strongly up‐regulated by CIT. In contrast, in old rats, while glyceroneogenesis was lower, beta‐oxidation was not affected, enabling increased FA release. Conclusion Hence, in visceral AT, CIT exerts a specific induction of the beta‐oxidation capacity in young rats and a selective stimulation of FA release in old rats, therefore providing a direct mechanism of CIT action to reduce AT mass.